Present and Future Therapeutic Approaches to Barrier Dysfunction - Fortea, Marina; Albert-Bayo, Mercé; Abril-Gil, Mar; Ganda Mall, John-Peter; Serra-Ruiz, Xavier; Henao-Paez, Alejandro; Expósito, Elba; González-Castro, Ana María; Guagnozzi, Danila; Lobo, Beatriz; Alonso-Cotoner, Carmen; Santos, Javier (Frontiers in Nutrition, 2021)
There is converging and increasing evidence, but also uncertainty, for the role of abnormal intestinal epithelial barrier function in the origin and development of a growing number of human gastrointestinal and extraintestinal inflammatory disorders, and their related complaints. Despite a vast literature addressing factors and mechanisms underlying changes in intestinal permeability in humans, and its connection to the appearance and severity of clinical symptoms, the ultimate link remains to be established in many cases. Accordingly, there are no directives or clinical guidelines related to the therapeutic management of intestinal permeability disorders that allow health professionals involved in the management of these patients to carry out a consensus treatment based on clinical evidence. Instead, there are multiple pseudoscientific approaches and commercial propaganda scattered on the internet that confuse those affected and health professionals and that often lack scientific rigor. Therefore, in this review we aim to shed light on the different options, which include, among others, dietary management, nutraceuticals and medical devices, microbiota and drugs, through an objective evaluation of the scientific publications in this field. Advances in the knowledge and management of intestinal permeability will sure enable better options of dealing with this group of common disorders to enhance quality of life of those affected.